2019
DOI: 10.4238/gmr18099
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Genotype x environment interactions and implications for associations among soybean traits

Abstract: An option into guide selection strategies in soybean breeding programs is to investigate associations between the main traits studied by breeders. A question that is faced is the possible influence of genotype x environment (GE) interactions on correlations among traits. Path analysis allows, in addition to measuring correlation, a more detailed study of cause / effect relationships among traits. We measured the effect of the GE interaction in the association between agronomic traits in soybeans. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The full maturity trait has direct relationships with flowering and grain yield; the earlier full maturity occurs, the earlier the flowering and the lower the grain yield (Table 4). Likewise, Enideg et al (2016), Gesteira et al (2018), and Pereira et al (2019 found a positive correlation between these traits.…”
Section: Resultsmentioning
confidence: 88%
“…The full maturity trait has direct relationships with flowering and grain yield; the earlier full maturity occurs, the earlier the flowering and the lower the grain yield (Table 4). Likewise, Enideg et al (2016), Gesteira et al (2018), and Pereira et al (2019 found a positive correlation between these traits.…”
Section: Resultsmentioning
confidence: 88%